Health and Economic Outcomes in the Alumni of the Wounded Warrior Project - Krull, Heather; Haugseth, Matthew Tyler (RAND Corporation, 2023)
The Wounded Warrior Project (WWP) provides those injured during service on or after September 11, 2001, access to programs that ensure that wounded warriors are well-adjusted in mind, spirit, and body and that they are economically empowered. Here the authors report a detailed analysis of how alumni were meeting these goals and how their outcomes compared with the outcomes of other veteran and nonveteran U.S. populations.